UPAYA MENINGKATKAN KUAT GESER TANAH LEMPUNG DENGAN MEMANFAATKAN LIMBAH PLASTIK - Endaryanta, Dian Eksana Wibowo (Universitas Negeri Yogyakarta, 2016)
ABSTRACTThe objectives of this study was to determine: (1) the effect of the addition of plastic waste ofmineral watercontainers (in some variations and percentages) to qu (the value of unconfined compressive strength) of clay, (2)the effect of the addition of the plastic waste to φ (the shear strength) of clay, (3) the effect of the addition of theplastic waste to c (the adhesiveness) of clay. This study applied anexperiment method. The plastics were cut intothe sizes of 1x1 cm and 1x0,5 cm, then they were mixed in the clay, compacted, and then tested. Theclaysamples were taken from Wates (Jl. Wates km 7) Kulonprogro and Kasongan Bantul at a depth of -0.20 m. Theplastic waste used was the mineral water container (PET plastic). The results showed that the addition of plasticwaste ofmineral water containers: (1) raises the value of qu (unconfined compressive strength) of the clay fromWates with 1% - 2% of plastics and the clay from Kasongan with 1% of plastics (2) raisesthe shear strength φ, ifthe level of plastics was 1% - 3% in the clay from Wates and Kasongan but if only the plastics were cut into smallpieces (c) decreases the adhesion, unless the plastic were in small sizes at the level of 3% (clay from Wates) andif the plastics were in large size (clay from Kasongan).Keywords: clay, plastic waste, unconfined compressive strengthABSTRAKPenelitian ini bertujuan untuk: (1) mengetahui pengaruh penambahan potongan limbah plastik wadah air mineral(pada beberapa variasi dan persentase) terhadap qu (nilai kuat-tekan-bebas) tanah lempung, (2) mengetahuipengaruh penambahan potongan limbah plastik terhadap φ (sudut kuat geser) tanah lempung, (3) mengetahuipengaruh penambahan potongan limbah plastik terhadap c (lekatan) tanah lempung.Penelitian ini menggunakanmetode Eksperimen. Limbah plastik dipotongukuran 1x1 (cm) dan 1x 0,5 (cm) kemudian dicampurkan pada tanahlempung, dipadatkan, lalu diuji kuat tekan bebasnya. Sampel lempung diambil dari Wates (Jl. Wates km 7)Kulonprogo dan Kasongan Bantul pada elevasi -0,20 m. Limbah Plastik menggunakan bekas wadah air mineral(plastik jenis PET).Hasil penelitian menunjukkan bahwa penambahan potongan limbah plastik ukuran tersebutpada lempung dapat: (1) menaikkan nilai qu (kuat tekan bebas) tanah pada kadar plastik 1%-2% lempung Watesdan kadar plastik 1% pada lempung Kasongan(2) menaikkan sudut-kuat-geser φ jika kadar plastik 1%-3%lempung Wates dan Lempung Kasongan tetapi hanya jika plastiknya dipotong kecil (c) menurunkan lekatan,kecuali jika potongan plastik ukurannya kecil pada kadar plastik 3% (lempung Wates) dan jika potongan plastikukurannya besar (lempung Kasongan).Kata kunci: lempung, limbah plastik, tekan bebas